Bipartite binding of the intrinsically disordered scaffold protein JIP1 to the kinase JNK1 - Thibault Orand; Elise Delaforge; Alexandra Lee; Jaka Kragelj; Maud Tengo; Laura Tengo; Martin Blackledge; Elisabetta Boeri Erba; Roger J. Davis; Andrés Palencia; Malene Ringkjøbing Jensen (Proceedings of the National Academy of Sciences, 2025)
Scaffold proteins are key players in many signaling pathways where they ensure spatial and temporal control of molecular interactions by simultaneous tethering of multiple signaling components. The protein JIP1 acts as a scaffold within the c-Jun N-terminal kinase (JNK) signaling pathway by assembling three kinases, MLK3, MKK7, and JNK, into a macromolecular complex that enables their specific activation. The recruitment of these kinases depends on the 450-amino acid intrinsically disordered tail of JIP1, however, the structural details of this tail and the molecular mechanisms by which it binds kinases have remained elusive. Here, we provide an atomic resolution structural description of the JIP1 tail, and we study its interaction with the kinase JNK1. Using NMR spectroscopy, we show that JNK1 not only engages with the well-known docking site motif (D-motif) of JIP1, but also interacts with a noncanonical F-motif. We determine the crystal structure of the JIP1–JNK1 complex at 2.35 Å resolution revealing a bipartite binding mode of JIP1. Our work provides insights into the sequence determinants of F-motifs suggesting that these motifs may be more prevalent in JNK substrates than previously recognized. More broadly, our study highlights the power of NMR spectroscopy in uncovering kinase interaction motifs within disordered scaffold proteins, and it paves the way for atomic-resolution interaction studies of JIP1 with its multitude of interaction partners.